Characterization and Online Detection of Surfactin Isomers Based on HPLC-MS(n) Analyses and Their Inhibitory Effects on the Overproduction of Nitric Oxide and the Release of TNF-α and IL-6 in LPS-Induced Macrophages - Tang, Jin-Shan (Molecular Diversity Preservation International, 2010)
A rapid method for characterization and online detection of surfactin isomers was developed based on HPLC-MS(n) (n = 1, 2, 3) analyses, and many surfactin isomers were detected and characterized from the bioactive fraction of the mangrove bacterium Bacillus sp. Inhibitory activities of surfactin isomers on the overproduction of nitric oxide and the release of TNF-α and IL-6 in LPS-induced macrophages were systematically investigated. It was revealed that the surfactin isomers showed strong inhibitory properties on the overproduction of nitric oxide and the release of IL-6 on LPS-induced murine macrophage cell RAW264.7 with IC(50) values ranging from 1.0 to 7.0 μM. Structure-activity relationship (SAR) studies revealed that the existence of the free carboxyl group in the structure of surfactin isomers was crucial. These findings will be very helpful for the development of this novel kind of natural product as new anti-inflammatory agents.